Peran PLUT - UMKM Dalam Proses Pendampingan dan Kerjasama Permodalan UMKM di Kabupaten Tulung Agung - Binti Nur Asiyah; Mashudi; Dwi Astuti Wahyu Nurhayati; Novi Tri Oktavia (Jurnal Ekuilnomi, 2023)
This study was triggered by the emerging of the developing of UMKM in Tulungagung Regency. UMKM or Usaha Mikro Kecil dan Menengah is considered as an economic unit which needs enhancement, guiding from related stakeholders in order to enable at earning products and service to sell towards the common people or community. This study deployed a descriptive qualitative method by displaying a case study design which showed research procedure and gained descriptive data as the written text. The study’s objective was to analyze the role of PULT-UMKM in enhancing UMKM in Tulungagung Regency. The result of study showed that PULT provided various services to UMKM entrepreneurship by delivering guidance facilitate business permit such as Business Identity Number (NIB), Food Household Industry (PIRT), Halal Certification and other permits in order to support UMKM products of Tulungagung Regency, including obtaining legalization and recognition of society that those products were affordable to consume. Besides, the guidance or enhancement of marketing of UMKM products digitally as well conventionally was done by PLUT-UMKM toward any in pursuance of increasing selling volume of UMKM Tulungagung Regency. Instead of those services, PLUT-UMKM also provides UMKM entrepreneurship to establish capitalization cooperation not only from financial or depository institutions but also non depository institutions (LKNB), including any assistance of the government and the Corporate Social Responsibility (CSR).